2018
DOI: 10.1044/2018_jslhr-l-17-0421
|View full text |Cite
|
Sign up to set email alerts
|

Structural Relationship Between Cognitive Processing and Syntactic Sentence Comprehension in Children With and Without Developmental Language Disorder

Abstract: Purpose We assessed the potential direct and indirect (mediated) influences of 4 cognitive mechanisms we believe are theoretically relevant to canonical and noncanonical sentence comprehension of school-age children with and without developmental language disorder (DLD). Method One hundred seventeen children with DLD and 117 propensity-matched typically developing (TD) children participated. Comprehension was indexed by children identifying the agent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
17
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 123 publications
3
17
0
7
Order By: Relevance
“…Still using a complex WM task (visual N-back), Weismer and colleagues (2017) found that WM performance predicts results in a grammatical judgment task, including omissions of verbal inflexions in complex sentences, in 30 children with language impairment (including participants with DLD and autism spectrum disorders; M age = 9;8). Finally, in a more recent study, Montgomery, Evans, Fargo, Schwartz, and Gillam (2018) found that complex working memory (assessed by two tasks involving concurrent processing and storage) mediates complex sentence comprehension (non-canonical sentences) in 117 children with DLD aged seven to eleven, whereas for canonical structures, these children seem to depend on long-term memory language knowledge.…”
Section: Working Memory and Syntaxmentioning
confidence: 94%
See 2 more Smart Citations
“…Still using a complex WM task (visual N-back), Weismer and colleagues (2017) found that WM performance predicts results in a grammatical judgment task, including omissions of verbal inflexions in complex sentences, in 30 children with language impairment (including participants with DLD and autism spectrum disorders; M age = 9;8). Finally, in a more recent study, Montgomery, Evans, Fargo, Schwartz, and Gillam (2018) found that complex working memory (assessed by two tasks involving concurrent processing and storage) mediates complex sentence comprehension (non-canonical sentences) in 117 children with DLD aged seven to eleven, whereas for canonical structures, these children seem to depend on long-term memory language knowledge.…”
Section: Working Memory and Syntaxmentioning
confidence: 94%
“…Until now, such a link between complex syntactic abilities and working memory in DLD has received relatively little attention (Durrleman & Delage, 2016;Frizelle & Fletcher, 2015;Marinis & Saddy, 2013;Montgomery & Evans, 2009;Montgomery et al, 2018). However, the implications of the presence of such a relationship seem to be of the utmost importance in the understanding, as well as in the remediation, of difficulties encountered by children with DLD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The findings from this study raise the possibility that this shorter protocol might be an effective tool when used in conjunction with traditional therapy where the client receives a very short session of HD tDCS stimulation combined with working memory training prior to the therapy session to induce short term improvement in working memory that would enhance the therapy session. For example, results from a recent large-scale study indicate that phonological working memory is a major factor in the successful comprehension of both simple and complex spoken sentences in both individuals with and without DLD ( Montgomery et al, 2018 ). The findings from the current study suggest that therapy sessions with individuals with DLD that are focused on improving comprehension of complex grammatical structures might benefit from the use of this HDtDCS phonological working memory protocol prior to the therapy session.…”
Section: Summary Of Results and Conclusionmentioning
confidence: 99%
“…덩이는 장기기억과 의 상호작용으로 생기는 단기기억에서의 용량 단위로 여겨진다 (Cowan, 2001;Miller, 1956). 이를 바탕으로 덩이짓기 능력은 개인 이 처음에 접하는 서로 다른 정보 항목(item)을 묶어, 더 적고 통합 된 단위로 처리할 수 있도록 도와주는 주요기능으로 (Montgomery, Evans, Fargo, Schwartz, & Gillam, 2018), 단어 또는 숫자와 같 은 여러 항목을 하나의 표상으로 통합하여 개인의 저장 용량을 확 장하는 역할을 한다 (Nobre et al, 2013).…”
unclassified